2008
DOI: 10.1055/s-2007-1004592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olanzapine on Slow Wave Sleep, Sleep Spindles and Sleep-Related Memory Consolidation in Schizophrenia

Abstract: Since not only slow wave sleep but also sleep spindles are supposed to promote sleep-related memory consolidation, we suggest that a putative positive effect on memory performance by slow wave sleep augmentation is neutralised by the decrease in sleep spindles due to olanzapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 43 publications
5
49
1
Order By: Relevance
“…Legault et al (721) reported that the dopamine receptor blocker flupenthixol infused into the dorsal striatum 0 -4 h after learning during "REM sleep windows" exerted the same impairing effect on habit consolidation as observed after scopolamine. In humans, so far only patients (with early Parkinson disease and schizophrenia) have been examined in this context with dopaminergic drugs that were partly rather unspecific (465,776). No consistent effects of the treatments on overnight retention of procedural or declarative memories were found in these patients.…”
Section: Neuro-and Hormonal Modulation Associated With Rem Sleep Andmentioning
confidence: 99%
“…Legault et al (721) reported that the dopamine receptor blocker flupenthixol infused into the dorsal striatum 0 -4 h after learning during "REM sleep windows" exerted the same impairing effect on habit consolidation as observed after scopolamine. In humans, so far only patients (with early Parkinson disease and schizophrenia) have been examined in this context with dopaminergic drugs that were partly rather unspecific (465,776). No consistent effects of the treatments on overnight retention of procedural or declarative memories were found in these patients.…”
Section: Neuro-and Hormonal Modulation Associated With Rem Sleep Andmentioning
confidence: 99%
“…SWS duration was positively correlated with memory performance in patients but not in controls (the lack of correlation in controls may have been due to a ceiling effect on performance). A subsequent study found that greater SWS duration was associated with better verbal declarative memory the following morning in chronically medicated schizophrenia patients (Göder et al 2008). Furthermore, enhancing slow waves using transcranial direct current stimulation during NREM sleep improved verbal memory retention in medicated schizophrenia patients (Göder et al 2013).…”
Section: Sleep-specific Eeg Rhythms In Schizophreniamentioning
confidence: 98%
“…This contrast with reports of disrupted sleep in SZ (reviewed above) may reflect that sleep disruption primarily characterizes more acute phases of SZ and that APDs are sedating and tend to normalize sleep architecture (18). The effects of chronic APD treatment on spindles are unknown but a single dose of olanzapine in SZ reduced spindle density (78), and acute administration of haloperidol to healthy participants did not affect spindle density (79). …”
Section: Sleep Spindle Deficit In Szmentioning
confidence: 99%